DIAGNÓSTICO DA GESTÃO DA MANUTENÇÃO PREDIAL DE UMA INSTITUIÇÃO FEDERAL DE ENSINO - Paes, Caroline Ornelas (2019)
Buildings in an organization are used to house productive activities. Such buildings are usually designed to have a long service life. High values are invested since the project stage. The main purpose of building maintenance is to maintain these building